Integrasi Kearifan Lokal Pada Pembelajaran di SD Melalui Etnomatematika dan Etnosains (Ethnomathscience) - Ratna Widyaningrum; Ema Butsi Prihastari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on an international survey, the performance of Indonesian students in mathematics and science is relatively low. So learning innovations are needed for enjoyable learning. Etnomathscience is a collaboration between ethnomathematics and ethnoscience so that local culture is integrated synergistically in learning. The achieved from this program are providing: 1) an understanding of Ethnomathscience, 2) skills for teachers in analyzing teaching material that can be integrated with the local culture. This service was carried out at SDN Prawit I Surakarta. The methods of service delivery include approach methods starting from the survey, licensing, and motivation; the implementation of the program including the preliminary stage, the stage of socialization and audience, the implementation phase, and the evaluation phase. The target is the participants can understand and can be integrated ethnomathscience in learning and have the skills in analyzing teaching material that can be integrated with the environment and local culture.